2013
DOI: 10.5194/bgd-10-6143-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Horizontal distribution of Fukushima-derived radiocesium in zooplankton in the northwestern Pacific Ocean

Abstract: The magnitude of the 9.0 Tohoku earthquake and the ensuing tsunami on 11 March 2011, inflicted heavy damage on the Fukushima Dai-ichi nuclear power plant (FNPP1). Fission products were emitted, falling over a broad range in the northern hemisphere, and water contaminated with radionuclides leaked into the ocean. In this study, we described the horizontal distribution of the Fukushima-derived radiocesium in zooplankton and in seawater in the western North Pacific Ocean (500–2100 km from the FNPP1) 10 months aft… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…North of 38 °N along the 155 °E transect, the FNPP-derived radiocaesium core was within CMW. These findings are consistent with those of previous studies 25 26 27 , which have reported the detection of 134 Cs in STMW around 149 °E in the winter of 2012, in STMW at 137 °E during April of 2012 and March of 2013 24 , and in CMW at 165 °E in June of 2012 30 . Concentrations of 137 Cs in the subsurface peaks in this and previous studies have also been roughly comparable, ranging between 5 and 15 Bq m −3 ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…North of 38 °N along the 155 °E transect, the FNPP-derived radiocaesium core was within CMW. These findings are consistent with those of previous studies 25 26 27 , which have reported the detection of 134 Cs in STMW around 149 °E in the winter of 2012, in STMW at 137 °E during April of 2012 and March of 2013 24 , and in CMW at 165 °E in June of 2012 30 . Concentrations of 137 Cs in the subsurface peaks in this and previous studies have also been roughly comparable, ranging between 5 and 15 Bq m −3 ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Concentrations of 137 Cs in the subsurface peaks in this and previous studies have also been roughly comparable, ranging between 5 and 15 Bq m −3 ( Fig. 3 ) 24 25 26 27 28 30 .…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations